2000
DOI: 10.1117/12.395586
|View full text |Cite
|
Sign up to set email alerts
|

<title>Multiple-resolution study of Ka-band HRR polarimetric signature data</title>

Abstract: SAR resolution and polarization performance studies for ATR algorithms have been the source of recent attention. Thorough investigations are often hindered by the lack of rigorously consistent high-resolution full-polarimetric signature data for a sufficient number of targets across requisite viewing angles, articulations and environmental conditions. While some evaluative performance studies of high-value structures and conceptual radar systems may be effectively studied with limited field radar data, to mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2001
2001
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Initially, the arithmetic mean and median of the azimuth averaged RCS turntable data were calculated for each signature measured using ERADS' compact range (CR) radar as shown in Tables To evaluate the impact of these differences on the signature-to-signature RCS variability of high-resolution field and scale-model imagery, an averaged percent difference (APD) algorithm, developed and detailed by STL researchers in prior signature investigations 5 was executed. The APD algorithm was implemented on the high resolution ISAR imagery at 1°a spect increments for the entire spin of the target (360 images) and angular adjustments were performed to minimize the APD, thus eliminating azimuth misalignment between signature sets.…”
Section: Analysis Of the Signature Measurementsmentioning
confidence: 99%
“…Initially, the arithmetic mean and median of the azimuth averaged RCS turntable data were calculated for each signature measured using ERADS' compact range (CR) radar as shown in Tables To evaluate the impact of these differences on the signature-to-signature RCS variability of high-resolution field and scale-model imagery, an averaged percent difference (APD) algorithm, developed and detailed by STL researchers in prior signature investigations 5 was executed. The APD algorithm was implemented on the high resolution ISAR imagery at 1°a spect increments for the entire spin of the target (360 images) and angular adjustments were performed to minimize the APD, thus eliminating azimuth misalignment between signature sets.…”
Section: Analysis Of the Signature Measurementsmentioning
confidence: 99%
“…1 Therefore, only a brief description will be given here. The ISAR images that result from the threshold method described in Step 2 are overlapped with each other using the location of the maximum correlation amplitude calculated in Step 4.…”
Section: Step 5 Calculate Isar Pixel Average Percent Differences (Apd)mentioning
confidence: 99%
“…Several test data collections were then performed on the 1/35 th scale model T72 in several different operational configurations, and in a complex two-target scene wherein it was mounted to the back of a much larger vehicle. A comparison of the ISAR images was performed similar to the correlation studies done in previous works 1,2,3 where ISAR images are correlated against each other to determine the quality of the match. It will be shown that the T72 data sets correlate very well even across different radar platforms.…”
Section: Introductionmentioning
confidence: 99%
“…The comparative methodology used to quantify the signature-to-signature conditions and environments RCS variability was originally developed by STL researchers for evaluating (and establishing similitude between) MMW and scaled submillimeter-wave radar measurements (5) . To quantify the impact of these differences, independently measured images were cross-correlated using an averaged percent difference (APD) algorithm (7) .…”
Section: Analysis Of the Signature Measurementsmentioning
confidence: 99%
“…(1,3,5,7) The program has concentrated on analyzing radar signatures from multiple main battle tanks (MBTs) in order to quantify the differences in Ka-band signatures of vehicles due to intraclass and interclass target variations. The metrics and model building procedures now provide the foundation for executing an analysis of target structures in operational environments.…”
mentioning
confidence: 99%